2008
DOI: 10.1007/s11627-008-9157-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving salinity tolerance in crop plants: a biotechnological view

Abstract: Salinity limits the production capabilities of agricultural soils in large areas of the world. Both breeding and screening germplasm for salt tolerance encounter the following limitations: (a) different phenotypic responses of plants at different growth stages, (b) different physiological mechanisms, (c) complicated genotype × environment interactions, and (d) variability of the salt-affected field in its chemical and physical soil composition. Plant molecular and physiological traits provide the bases for eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(151 citation statements)
references
References 111 publications
4
132
0
4
Order By: Relevance
“…Salinity due to the over-accumulation of NaCl is usually of great concern and is the most damaging factor in arid and semi-arid regions. Saline soils are widespread throughout the world, and their genesis may be natural or accelerated by irrigated agriculture, the intensive use of water resources combined with high evaporation rates and human activity (Lambers, 2003;Arzani, 2008). The osmotic adjustment, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity due to the over-accumulation of NaCl is usually of great concern and is the most damaging factor in arid and semi-arid regions. Saline soils are widespread throughout the world, and their genesis may be natural or accelerated by irrigated agriculture, the intensive use of water resources combined with high evaporation rates and human activity (Lambers, 2003;Arzani, 2008). The osmotic adjustment, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Arzani (2008) found that the net photosynthesis rate and growth of plant reduced because of salinity. Misra et al (1997) and Munns et al (2002) also found that various parameters about photosynthesis, such as the potential of leaf moisture, the composition of pigment, the heat of leaf and the relative water content of leaf, were changed by salinity.…”
Section: Discussionmentioning
confidence: 99%
“…These genotypes may have carried useful genes that would be expressed in other target environments. Owing to the gains in speeded up cultivar development and the creation of desirable genetic backgrounds, doubled haploids are widely utilized in breeding as well as in genetic studies of various crops and traits [16]; [17]; [18] and [19]. Overall, the DH technology allows for the creation of stable haploids after recombination of parents with broad genetic variation.…”
Section: Doubled Haploid Breeding Methodsmentioning
confidence: 99%